From Meaning of Working to Meaningful Lives: The Challenges of Expanding Decent Work - Annamaria Di Fabio (Frontiers Research Topics, 2016)
This Research Topic explores issues that are central to the continued relevance of organizational and vocational psychology, and equally central to the well-being of individuals and communities. The cohering theme of this publication revolves around the question of how people can establish meaningful lives and meaningful work experiences in light of the many challenges that are reducing access to decent work. Another essential contextual factor that is explored in this volume is the Decent Work Agenda (International Labour Organization, 2008), which represents an initiative by the International Labour Organization. In this book, we hope to enrich the Decent Work Agenda by infusing the knowledge and perspectives of psychology into contemporary discourses about work, and well-being. Another inspiration for this project emerged from the UNESCO Chair in Lifelong guidance and counseling, recently established in Poland in 2013 under the leadership of Jean Guichard, which has focused on advancing research and policy advocacy about decent work. This new era calls for an innovative perspective in constructing decent work and decent lives: the passage from the paradigm of motivation to the paradigm of meaning, where the sustainability of the decent life project is anchored to a meaningful construction. During this period when work is changing so rapidly, leaving people yearning for a sense of connection and meaning, it's fundamental to create a framework for an explicitly psychological analysis of decent work.